Politik Hukum Terhadap Sistem Hukum Negara Kesatuan Republik Indonesia Dalam Menjamin Kepastian Hukum - Ni Ketut Tri Srilaksmi (Satya Dharma : Jurnal Ilmu Hukum, 2022)
Politics cannot be separated from human action itself. In the legal system in Indonesia itself, politics is the main space in running the wheels of government and the government system. The Third Amendment to the Constitution of the Unitary State of the Republic of Indonesia in Chapter I Article 1 paragraph (3), reaffirms that "the State of Indonesia is a State of Law" (UUD 1945, 1945). The meaning of the rule of law is a state based on law. By stating that Indonesia is rechtsstaat, it means that the state is not based on power. The power possessed by the government is the power granted by the law. However, in the implementation of a rule so that the country can move, it is necessary to have a policy in regulating the rhythm of the country's travel. To maintain the political climate, legal certainty is needed in building the corridor. Indonesia itself in the last 10 years has experienced a fairly tiring political change. Starting from the gubernatorial election of Jakarta to the politics of the presidential election, the elections which are held every 5 years build legal politics that are not conducive. So how can the constitution protect Indonesian politics? This problem will be studied and discussed in this study. Using normative research methods will dissect the political concept itself. In addition to the political concept, the concept of power and sources of power will also be discussed as one of the goals of politics itself, resulting in political influence on law and legal certainty in Indonesia.